Mathematical correction of the effects of storage time and gas contamination on blood sample measurements - Nevirian, Bahareh; Thomsen, Lars Pilegaard; Fagerberg, Steen Kåre; Nybo, Jette; Pedersen, Mette Krogh; Damgaard, Kjeld Asbjørn Jensen; Shastri, Lisha; Kristensen, Søren Risom; Rees, Stephen Edward (Frontiers in Medicine, 2025)
ObjectiveAnalysis delay and gas contamination can affect the accuracy of blood measurements. This study uses a mathematical model of blood acid-base chemistry and gas in the sample tubes to calculate values of pH, partial pressures of carbon dioxide (pCO2), partial pressure of oxygen (pO2), oxygen saturation in whole blood (SO2), glucose, and lactate at sample time from measurements with delayed analysis and gas contamination.MethodsData were analyzed from two published studies. Study 1: Samples were obtained from 30 critically ill patients in standard blood gas syringes and analyzed after 0, 36, 54, 72, 90, 108, 126, 144, 162, and 180 min. Study 2: Samples were taken from 20 healthy participants in standard blood gas syringes and vacuum tubes (2 mL and 4 mL) and analyzed after 0, 20, and 90 min. Calculated values from the mathematical model were compared to measured values at sample time.ResultsFor delays of up to 90 min, the accuracy (mean) and precision (standard deviation (SD)) values calculated at the sample time using syringes and 4-mL vacuum tubes remained within clinically acceptable limits when compared to measured values, with the exception of SO₂ in vacuum tubes. Values represent the mean difference ± standard deviation between calculated and measured values. For syringes, the results were as follows: pH = −0.004 ± 0.011, pCO₂ = 0.08 ± 0.18 kPa, pO₂ = 0.05 ± 0.34 kPa, SO₂ = 0.39 ± 2.21%, glucose = 0.07 ± 0.35 mmol/L, and lactate = 0.13 ± 0.22 mmol/L. For 4-mL vacuum tubes, the results were as follows: pH = 0.006 ± 0.007, pCO₂ = −0.07 ± 0.11 kPa, pO₂ = −0.37 ± 0.34 kPa, SO₂ = −7.79 ± 4.95%, glucose = 0.01 ± 0.11 mmol/L, and lactate = −0.00 ± 0.20 mmol/L. In addition, 2-mL vacuum tubes had poorer accuracy and precision values than syringes and 4-mL vacuum tubes in a subset of cases.ConclusionThis study has shown that a mathematical model can accurately and precisely calculate blood values at sample time, even following delayed analysis, using both standard blood gas syringes and selected vacuum tubes. This method may have clinical applications in improving the logistics of blood sampling and analysis.